1H NMR of paramagnetic Dy3+ complex with DTPA-amide p-xylylene-cyclophane; possible probing action toward d-histidine and histamine. (1st May 2020) - Elena Navarro, Rosa; Serna-Medina, Octavio; Soberanes, Yedith; Cabellos, José Luis; Inoue, Motomichi; Santacruz, Hisila; Posada-Amarillas, Álvaro
Graphical abstract: The highly rigid p-xylylene cyclophane forms largely distorted coordination geometry in the Dy 3+ complex. This structural feature results in the pseudocontact shifts with narrow linewidths. The large open space around the metal ion accommodates water molecules and is able to capture a histamine or histidine molecule when it coexists. Abstract: As an effort to search for paramagnetic probing agents toward specific substrates, 1 H NMR studies were carried out on the Dy 3+ complex of a chelating cyclophane derived from DTPA (diethylenetriaminepentaacetate) and p -xylylenediamine, and the paramagnetic effects were examined on coexisting d -histidine and histamine. The lanthanide metal complex exhibits well-defined paramagnetic shifts of the psuedocontact term, owing to the highly rigid macrocyclic framework. Coexisting histamine and histidine also show sharp NMR peaks with small but significant shifts, in contrast to the spectra in the coexistence of the free metal ion. The metal chelate molecule has a large open space, in which a substrate molecule is captured and exchanged with nearby molecules. Through this exchange process, the spatial paramagnetic effect of the metal chelate extends in a long range so that coexisting substrate molecules can be probed by NMR.